Magnetic responsive materials modulate the inflammatory profile of IL-1β conditioned tendon cells. (November 2020) - Vinhas, A.; Rodrigues, M.T.; Gonçalves, A.I.; Reis, R.L.; Gomes, M.E.
Abstract: Tendinopathies represent half of all musculoskeletal injuries worldwide. Inflammatory events contribute to both tendon healing and to tendinopathy conditions but the cellular triggers leading to one or the other are unknown. In previous studies, we showed that magnetic field actuation modulates human tendon cells (hTDCs) behavior in pro-inflammatory environments, and that magnetic responsive membranes could positively influence inflammation responses in a rat ectopic model. Herein, we propose to investigate the potential synergistic action of the magnetic responsive membranes, made of a polymer blend of starch with polycaprolactone incorporating magnetic nanoparticles (magSPCL), and the actuation of pulsed electromagnetic field (PEMF): 5 Hz, 4mT of intensity and 50% of duty cycle, in IL-1β-treated-hTDCs, and in the immunomodulatory response of macrophages. It was found that the expression of pro-inflammatory ( TNFα, IL-6, IL-8, COX-2 ) and ECM remodeling ( MMP-1, -2, -3 ) markers tend to decrease in cells cultured onto magSPCL membranes under PEMF, while the expression of TIMP-1 and anti-inflammatory genes ( IL-4, IL-10 ) increases. Also, CD16 ++ and CD206 + macrophages were only found on magSPCL membranes with PEMF application. Magnetic responsive membranes show a modulatory effect on the inflammatory profile of hTDCs favoring anti-inflammatory cues which is also supported by the anti-inflammatory/repair markers expressed in macrophages. These results suggest that magnetic responsive magSPCL membranes can contribute for inflammation resolution acting on both resident cell populations and inflammatory cells, and thus significantly contribute to tendon regenerative strategies. Statement of significance Magnetically-assisted strategies have received great attention in recent years to remotely trigger and guide cell responses. Inflammation plays a key role in tendon healing but persistent pro-inflammatory molecules can contribute to tendon disorders, and therefore provide a therapeutic target for advanced treatments. We have previously reported that magnetic fields modulate the response of human tendon cells (hTDCs) conditioned to pro-inflammatory environments (IL-1β-treated-hTDCs), and that magnetic responsive membranes positively influence immune responses. In the present work, we combined pulsed electromagnetic field (PEMF) and magnetic responsive membranes to guide the inflammatory profile of IL-1β-treated-hTDCs and of macrophages. The results showed that the synergistic action of PEMF and magnetic membranes supports the applicability of magnetically actuated systems to regulate inflammatory events and stimulate tendon regeneration. Graphical abstract: Image, graphical abstract